Optimasi Ekonomi Berkelanjutan UMKM Kelurahan Gunung Anyar Tambak Melalui Sosialisasi dan Pendampingan Sertifikasi Halal - Putri, Devita Wahyu Aulia; Sholihah, Dewi Deniaty (As-Syirkah: Islamic Economic & Financial Journal, 2024)
Micro, Small and Medium Enterprises (MSMEs) have an important role in local economic growth, including in Gunung Anyar Tambak Village. Halal certification has an important role in business sustainability, access to wider markets, increasing competitiveness, adding value to products, and access to financing and government support for MSMEs. However, many MSMEs in Gunung Anyar Tambak Village still do not have halal certification for their food products. This activity aims to increase understanding and assistance as an effort to optimize the sustainable economy of MSMEs. Halal certification also supports the goals of SDGs point 8 regarding sustainable economic growth. Through halal certification assistance, MSMEs are expected to increase their competitiveness, reach more marketers, and contribute to inclusive and sustainable economic growth.